Sistem Pendukung Keputusan Penentuan Penerima Beasiswa Pendidikan Dengan Metode Simple Additive Weighting (Studi Kasus SMP Al Hikmah) - Noor Hasan - UBSI Yogyakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
Abstract - Al Hikmah Middle School as one of the education providers provides several scholarships to its students, educational scholarships become one of the scholarships that can be obtained by students. The large number of applicants who apply for scholarships makes it difficult for officers to select students who deserve to receive educational scholarships in accordance with applicable regulations. To support the process of selecting scholarships, a computer-based system can be made to make decisions that are known as Decision Support Systems (SPK). The system is designed using the Simple Additive Weighting (SAW) method. The purpose of this study is to make a decision support system for determining the recipients of educational scholarships using the simple additive weighting (SAW) method. This Decision Support System uses criteria, models, and assessments filled in by the principal. For the screening process scholarships are carried out by officers. Based on the tests made using the simple additive weighting method, it can be used to make decisions in selecting eligible students to get educational scholarships. This is proven by the criteria value and the level of importance needed in this study.Keywords: Decision Support System, Educational Scholarship, Simple Additive Weighting Abstraksi - SMP Al Hikmah sebagai salah satu penyelenggara pendidikan memberikan beberapa beasiswa kepada peserta didiknya, beasiswa pendidikan menjadi salah satu beasiswa yang dapat diperoleh siswa. Banyaknya pendaftar yang mengajukan beasiswa membuat petugas kesulitan untuk menseleksi siswa yang layak mendapatkan beasiswa pendidikan sesuai dengan ketentuan yang berlaku. Untuk mendukung proses menseleksian beasiswa dapat dibuat suatu sistem berbasis komputer untuk mengambil keputusan yang di kenal dengan Sistem Pendukung Keputusan (SPK) Sistem ini dirancang dengan menggunakan metode Simple Additive Weighting (SAW). Tujuan penelitian ini adalah membuat sistem pendukung keputusan penentuan penerima beasiswa pendidikan menggunakan metode simple additive weighting (SAW). Sistem Pendukung Keputusan ini menggunakan kriteria, model, serta penilaian yang diisi oleh kepala sekolah. Untuk proses penyaringan beasiswa dilakukan oleh petugas. Berdasarkan pengujian yang dibuat dengan metode simple additive weighting dapat digunakan untuk mengambil keputusan dalam menseleksi siswa yang layak untuk mendapatkan beasiswa pendidikan. Hal ini di buktikan pada nilai kriteria dan bobot tingkat kepentingan yang dibutuhkan pada penelitian kali ini.Kata Kunci: Sistem Pendukung Keputusan, Beasiswa Pendidikan, Simple Additive Weighting